EVALUASI PENANGANAN LIMBAH INFEKSIUS DI RSUD IBNU SINA GRESIK - Putri Nur Rohmah; Khambali; Demes Nurmayanti (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2021)
RSUD Ibnu Sina Gresik is a hospital with outpatient, inpatient and various health services which produces infectious waste of 245.5 kg/day. Infectious waste handling found discrepancies such as absence of a special route for transportation, and TPS building close to food vendors. The purpose of this study was to evaluate handling of infectious waste in RSUD Ibnu Sina Gresik. This type of research is descriptive with a cross sectional research approach. Primary data collection methods include observation, interviews, assessments that produce a good percentage, sufficient, less then SWOT analysis. The results of study produced a waste volume of 245.5 kg. Factors that affect human resources and infrastructure are accordance with provisions of regulations. Waste management is good category with a percentage of 80% applicable regulations. SWOT analysis found strategies to take advantage of strengths and opportunities such as improving quality of human resources, adding infrastructure according to standards, increasing supervision infectious waste management and knowledge of use Personal Protective Equipment for infectious waste handling officers. The conclusion of this study is that handling infectious waste is in accordance with provisions of regulations, but there are still some things that need to be improved such as monitoring officers on the use Personal Protective Equipment with socialization activities and giving rewards, increasing training activities for officers carried out by hospitals with socialization and workshops and means of transportation cleaning and provision of infrastructure for special routes for transportation and repair of TPS locations.